2017
DOI: 10.1183/13993003.02102-2016
|View full text |Cite
|
Sign up to set email alerts
|

QuantiFERON test interpretation in patients receiving immunosuppressive agents: an alert

Abstract: Latent tuberculosis infection (LTBI) diagnosis in immune-mediated inflammatory diseases is complex because of the patient characteristics and the imperfection of available tests [1]. Functional T-cell assays are exposed to bias at several levels (manufacturing, pre-analytical, analytical and immunological) [2] and, unfortunately, the lack of a gold standard precludes higher diagnostic accuracy. However, the QuantiFERON GOLD In-tube test (QFT; QIAGEN, Hilden, Germany) represents a largely used and modern altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Westall et al revealed that IFN-γ levels in response to mitogen measured with the QuantiFERON ® -CMV assay (Cellestis Ltd., Melbourne, Australia) were often negative after early lung transplant, because of immune suppression (14). Changes in IFN-γ levels in response to mitogen may depend on the immune system condition of the individual patient (15). In our study, low IFN-γ levels in response to mitogen before ICIs may also indicate the suppressed immune system state, which could Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…Westall et al revealed that IFN-γ levels in response to mitogen measured with the QuantiFERON ® -CMV assay (Cellestis Ltd., Melbourne, Australia) were often negative after early lung transplant, because of immune suppression (14). Changes in IFN-γ levels in response to mitogen may depend on the immune system condition of the individual patient (15). In our study, low IFN-γ levels in response to mitogen before ICIs may also indicate the suppressed immune system state, which could Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…The CCI, as adapted by Deyo et al [ 15 ], was utilized to assess the level of general comorbid medical conditions. In this study, we also adjusted for medications that may increase infection risk, including corticosteroids and immunosuppressive agents, including azathioprine, methotrexate, and cyclophosphamide [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…A low IFN-γ response to mitogen (<0.5 IU/mL) indicates an indeterminate result when a blood sample also has a negative response to the TB antigens. This pattern may occur with insufficient lymphocytes, reduced lymphocyte activity due to improper specimen handling, or an inability of the patient's lymphocytes to generate IFN-γ [23].…”
Section: Medical Frameworkmentioning
confidence: 99%
“…The reported prevalence of indeterminate results is higher in patients with chronic inflammatory conditions compared to healthy people. Also, patients who receive at least one immunosuppressive drug (especially steroids) are more likely to have an indeterminate result [23,24].…”
Section: Medical Frameworkmentioning
confidence: 99%